Platelet-white cell ratio is more strongly associated with mortality than other common risk ratios derived from complete blood counts - Brody H. Foy; Jonathan C. T. Carlson; Aaron D. Aguirre; John M. Higgins (Nature Communications)
Abstract Complete blood count indices and their ratios are associated with adverse clinical outcomes for many acute illnesses, but the mechanisms generating these associations are not fully understood. Recent identification of a consistent pattern of white blood cell and platelet count co-regulation during acute inflammatory recovery provides a potentially unifying explanation. Here we show that the platelet-to-white-cell ratio, which was selected based on this conserved recovery pattern, is more strongly associated with mortality than other blood count markers and ratios in four important illnesses involving acute inflammation: COVID-19, acute heart failure, myocardial infarction, and stroke. Patients recovering well from these acute illnesses tend to follow a joint white cell and platelet trajectory that can be reduced to this one-dimensional ratio. The platelet-to-white-cell ratio’s association with prognosis is consistent with recently identified inflammatory dynamics and may provide a convenient and interpretable summary of patient inflammatory state.